VOLATILITAS PEMILIH DAN INTERSEP POLITIK DALAM PEMILU DPRD KABUPATEN DEMAK 2004-2019 - Joko Juli Prihatmoko; Agus Riyanto (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
This study aims to determine the volatility of political parties, find the dynamics behind volatility, including intercept patterns or shifting political choices based on the social division of party voters in the 2004-2019 Demak DPRD elections. The type of research used is qualitative research combined with qualitative in numeric with a descriptive approach. The study found that the volatility index of the Demak DPRD elections was high and fluctuating, with an average of 34.26 in the last four elections. In the 2004 election, the volatility index was 53.36, declined to 22.93 in the 2014 election, and rose again to 26.51 in the 2019 election. The comparison of the level of electoral volatility shows differences in the stability of the pattern of competition between parties in the region, which further has consequences for local democratic politics. While high volatility shows the weakness of party and constituent relations, party institutionalization, and Party ID, which brings less stable election results while showing a more open and unpredictable electoral market. High vote volatility is reciprocally related to political intercepts, where one party bypasses or cuts off (growth) another party. Initially, political interception occurs across and between national or religious group parties, with national group parties getting the blessing of vote spillover from religious parties. Later, as the institutionalization of the religious group parties (PKB, PPP, and PAN) stabilized, political interception occurred between national group parties. It is easier for voters of national parties (PDIP, Gerindra, Golkar, Demokrat, Nasdem, etc.) to switch their choices. This confirms the openness of the electoral market for national group parties, which allows the emergence of new parties with large votes. Extrapolating, the shift in political choices will continue to occur in line with the increase in voter rationality. The biggest challenge is that the influence and size of the rational voter group is far below the fanatical rational voters and especially primordial voters. In addition, structural conditions are a barrier to increasing voter rationality as political forces that maintain primordialism to gain and maintain power strengthen